The urban heritage of Jakarta. Recovery of Kota's urban memory (Bulletin KNOB, 1991)
If guide-lines for re-planning stay out, the structure and form of Old Batavia will be wiped out for good. At present an ambitious project of the Indonesian and Dutch ministries to the reorganization of Jakarta's northern border compares the meaning of Kota as a historic nucleus with her value to Jakarta the metropolis.The urban heritage research divides the old town into parcels and lots. The historic features of these parcels and fragments of buildings, the present morphological characteristic and functional potencies of buildings and urban space to renewal and urban function were analyzed. The historic value of the plan and its contribution to the historic town as a whole has been weighed. This way every block was researched after three themes: historic development and background: present situation both and functional and morphological characteristic.The program of the preservation of Kota as a historic town and on the other hand the re-organization after a revised plan with a high future value are both meant to revitalize the old town. This revitalization also means that the raising of the functional value of the old town is coupled to a high value of experience of space and buildings, which experience is almost completely defined by Kota's historic character.To the preservation of Kota as a historic town strengthening of the original plan is necessary. The building-blocks however must preserve possibilities for development at the same time. In a historic basic or memory map of Kota the historic plan, objects and historic features have been made visible. These aspects are the starting point of the program for a revised town plan.Also the morphological characteristics of space and buildings are important. The contribution of each of the town-blocks to the coherent whole hereby is central. Because of Kota's historic orientation to the sea as an unmistakable datum of her urban identity the block of Pasar Ikan plays a vital role in the town plan.To be able to determine the nature and scope of the functional transformations which are necessary for a durable revitalization, Kota's role on the level of the metropolis Jakarta must be considered anew. Kota's geographic situation contains unique possibilities. The present gudang or warehouse-function of Kota will have to be replaced by a more dynamic and productive usage. Regional reflection on Kota will have to reconsider the meaning of Kota as a historic nucleus in the metropolis Jakarta and within the continually extending megatown JABOTABEK.Next to the two historic axes (one of these the axe of the completed fortification Kota), the third early 19th century axe can gain in meaning as a spatial identity-axe to a growing Jabotabek. This axe also has potency to be developed into a program for cultural tourism to the former islands of the Dutch United East-Indian Company.